GEMALA SEBAGAI ALTERNATIF PROGRAM LITERASI MENUMBUHKAN MINAT SISWA MENGAPRESIASI CERPEN - Susi Herlina; Jaja Wilsa (CV. ADIBA AISHA AMIRA, 2024)
The purpose of this research is to knowing the interest of SMPN 2 Lemahabang students in appreciating short stories and (2) knowing the response of SMPN 2 Lemahabang students to the implementation of Gemala as an alternative literacy program in fostering interest in appreciating short stories and (3) describing the form of appreciation of SMPN 2 Lemahabang students in writing short stories after participating in Gemala activities. The research method uses descriptive qualitative research. This study aims to find out Gemala as an alternative literacy program to foster students' interest in appreciating short stories. Data collection techniques in this study were interviews, questionnaires, and tests. The result of this study is the lack of interest of students in appreciating short stories because there are difficulties faced by students when writing short stories. After implementing the Gemala program, it was found that students' interest in short story appreciation increased. In addition, there is an analysis of short stories by students by paying attention to several aspects, namely: the suitability of the theme with the content of the short stories, the choice of words, rhymes, atmosphere, and messages contained in these short stories so that in this study Gemala can be an alternative literacy program to foster students' interest in appreciating short stories.